STRATEGI PEMBELAJARAN PPKn PADA PEMAHAMAN BELA NEGARA SISWA KELAS VIII DI SEKOLAH INKLUSI SMP MUHAMMADIYAH 2 KEDIRI - Komang Azalia Armaida; Oksiana Jatiningsih (Kajian Moral dan Kewarganegaraan, 2023)
The purpose of this study is to describe the strategies used by teachers to provide an understanding of state defense for Children with Special Needs (CSN) in inclusive classes. This study uses a qualitative approach with a descriptive method which takes place at SMP Muhammadiyah 2 Kediri. This study uses Peaget's cognitive learning theory. The focus of this research is a strategy that includes planning and implementation by teachers to provide an understanding of defending the country in inclusive classes consisting of regular children and special needs children. The subjects in this study were a class VIII Civics teacher who taught inclusive classes and a class assistant teacher. Data collection techniques used in this research are participant observation, semi-structured interviews and documentation in the form of lesson plans and the results of learning scores. Based on the research results, the implementation of PPKn learning begins with making a learning implementation plan which is the same as between ABK and regular students, but in the implementation of learning for regular students it is adjusted to the RPP and for ABK modifications are made to the RPP according to their needs. In the implementation of learning the teacher also manages the class to make it easier for children with special needs to receive the stimulus provided by the teacher. The teacher provides an understanding of defending the country by interpreting the national anthem, delivering repeated material and demonstrations, delivering material in verbal and non-verbal languages, optimizing the understanding of defending the country with image media, and implementing school rules as a form of love for the homeland.Kata Kunci: National Defense, Children in Need Special (CNS), Inclusive School.